A unique green-emitting phosphor-in-glass (PiG) for solid state laser lighting and displays. Issue 37 (24th August 2021) - Liang, Yueyuan; Bao, Shuyang; Zhang, Yujie; Xu, Fucai; Liang, Xiaojuan; Xiang, Weidong
Abstract : To further demonstrate the potential for solid-state laser lighting applications, the optical performances of (BaSr)2 SiO4 –PiG are explored under blue laser irradiation. Abstract : Heat-resistant fluorescent glass is an ideal color converter for laser lighting applications. However, the application requirements of high-quality laser lighting are difficult to meet due to the insufficient availability of cyan, green and red emission components. Therefore, the development of fluorescent green glass with high thermal stability and high brightness is the key core technology in the fields of laser lighting and display projection. In this research, a series of green-emitting (BaSr)2 SiO4 –PiG samples with high quantum efficiency were successfully prepared by dispersing (BaSr)2 SiO4 phosphor in a SiO2 –B2 O3 –CaO–Na2 O glass matrix. Meanwhile, the thermal stability, photoluminescence properties, and applicability of (BaSr)2 SiO4 –PiG in solid-state laser lighting applications have been monitored for the first time. Surprisingly, the thermal conductivity of (BaSr)2 SiO4 –PiG is 1.87 W m −1 K −1 at room temperature, which is much higher than that of other multicomponent glasses. Furthermore, under 2.69 W mm −2 blue laser incident power density excitation, a maximum luminous flux of 196.7 lm is achieved. More importantly, (BaSr)2 SiO4 –PiG exhibits an excellent luminous efficiency of 98 lm W −1 at a laser incident power density of 2.09 W mm −2 . Based on these investigations, (BaSr)2 SiO4 –PiG would be a reliable and efficient candidate as a green color converter for laser lighting and displays.